Spontaneous Perirenal Urinoma Associated with Ureteropelvic Junction Obstruction in a Child: A Case Report - Po-Chang Tseng; Tao-Yuan Liu; Shih-Jin Pan; Dyi-Shiang Sung (Pediatrics and Neonatology)
We report a case of a 10-year-old Taiwanese boy with a perinephric urinoma, whose health had previously been good, but who experienced a sudden onset of severe left flank pain. Radiological examination revealed ureteropelvic junction obstruction with grade IV hydronephrosis and perinephric urinoma of the left kidney. Percutaneous drainage was performed successfully to relieve these symptoms. Urinoma is a rare complication of congenital obstruction of the urinary tract, and it occurs most commonly following renal trauma.